Nación y subalternidades en los libros escolares del siglo XXI: una mirada crítica desde la “Campaña del Desierto” (Clío & Asociados. La historia enseñada, 2025)
This article analyzes some perspectives, changes, and continuities in the content of History subject at the high school in the province of Buenos Aires, usingthe nation and nationalism conceptions and representations. To this end, the text examines a selection of textbooks intended for third-year students of the "Nueva Escuela Secundaria" in Argentina. The "Campaña del Desierto," which took place in the last quarter of the 19th century in the south of what is now Argentina, is a privileged lens for approaching to issues such as nation, nationalism, and the place of subaltern groups in 21st-century school education are constructed and addressed.